Twice-daily Budesonide 2-mg Foam Induces Complete Mucosal Healing in Patients with Distal Ulcerative Colitis - Naganuma, Makoto (J Crohns Colitis, 2016)
BACKGROUND AND AIMS: Mucosal healing is an important therapeutic goal for ulcerative colitis. Once-daily administration of budesonide 2-mg foam is widely used for inducing clinical remission. No study has assessed the usefulness of twice-daily budesonide 2mg foam on mucosal healing in ulcerative colitis patients. We explored the efficacy for mucosal healing of once- or twice-daily budesonide foam in distal ulcerative colitis patients. METHODS: This study was a multicentre, randomised, double-blind, placebo-controlled trial. In all, 165 patients with active, mild to moderate distal ulcerative colitis were randomised to three groups: once- or twice-daily budesonide 2mg/25ml foam, or placebo foam, for 6 weeks. Complete mucosal healing [endoscopic subscore = 0] and the safety profile were assessed at Week 6. Prespecified and post hoc analyses were used. RESULTS: The percentages of complete mucosal healing in the twice-daily budesonide foam group were 46.4% compared with 23.6% in the once-daily group [p = 0.0097], or 5.6% in the placebo group [p < 0.0001]. The percentages of clinical remission and the percentages of endoscopic subscore ≤ 1 in the twice-daily budesonide foam group were 48.2% and 76.8%, compared with 50.9% and 69.1% in the once-daily group [no difference], or 20.4% and 46.3% in the placebo group [p = 0.0029 and p = 0.0007], respectively. In the subgroup of patients with previous use of a 5-aminosalicylic acid suppository or enema, there was a greater percentage of complete mucosal healing in the twice-daily budesonide foam group [32.0%] compared with that in the once-daily [8.7%, p = 0.0774] or placebo groups [4.8%, p = 0.0763], though there was no significant difference. No serious adverse event occurred. CONCLUSIONS: A significantly greater percentage of patients receiving twice-daily administration of budesonide foam compared with once-daily administration/placebo achieved complete mucosal healing. This is the first study to evaluate the endoscopic efficacy of twice-daily administration of 6-week budesonide foam treatment for ulcerative colitis.